Understanding the Factors Affecting the Small and Medium Enterprises Adoption of Cloud computing: A Literature Review - Nguyen, Giang Thi; Liaw, Shu-Yi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
Cloud computing is increasingly popular and brings many benefits to organizations. However, the adoption of cloud computing (CC) is influenced by many different factors. The current study is based on the Technology-Environment-Organization (TOE) framework to discover the influencing factors in the decision to adopt CC in SMEs. Quantitative methods have been used to analyze relevant articles. The findings of this study suggest that 28 factors influence the decision to adopt CC in SMEs. Moreover, top management support, technology readiness, security concern, and relative advantage have a stronger impact on CC adoption in SMEs. The findings of this study add to the present CC literature and help practitioners better comprehend the elements that drive CC adoption. As a result, they can develop a clear strategy for enhancing CC adoption in their enterprises